Modern condition of the problem of Lime Burreliosis of animals (systematic review) - Panteleenko O.; Yarchuk B.; Tsarenko T. (Науковий вісник ветеринарної медицини, 2021)
Lyme borreliosis (LB) is the most common tick-borne disease in the temperate climate of the Northern Hemisphere. LB is caused by spirochetes, which are grouped in the complex Borrelia burgdorferi sensu lato, vectors – Ixodidae mites, dozens of species of small mammals and birds actas reservoir hosts, and the role of reservoirs of domestic animals, such as dogs and cats, is not excluded. Although the ecology and epidemiology of the disease have been extensively studied in Europe and North America, there is considerable uncertainty regarding the study of Lyme borreliosis in veterinary medicine. Search, selection andanalysis of scientific data on the research topic were carried out according to acceptable rules for systematic reviews of the literature. The scientometric database Web of Science Core Collection, the database of scientific articles Pub Med and the database Scientific Periodicals of Ukraine were used. Seventy-four scientific articles were used for the article, which contained the necessary set of data and met the set goal. The article highlights the main issues of the etiology of the disease, which describes the characteristics of the pathogen, its properties, genotypic composition of Borrelia, which cause Lyme disease, the spread of pathogenic genotypes of Borrelia in Europe and Ukraine. The connection of Lyme borreliosis spread with ecological factors, climatic changes and anthropogenic impact on biocenoses and biotopes, the role of vectors and reservoir hosts in the spread of LB is described. Data on the prevalence and degree of infection of Ixodes mites with Borrelia, as well as the spread of LB among the population of Europe and Ukraine are presented. The seroprevalence of each of the animal species (dogs, cats, horses, ruminants), clinical manifestations of LB, if documented and indicators of LB prevalence among animals in Europe and Ukraine, as well as currently known treatments, prevention and diagnosis of LB animals are considered.